2008
DOI: 10.1007/s10295-008-0482-y
|View full text |Cite
|
Sign up to set email alerts
|

Production of xylanase by Aspergilli using alternative carbon sources: application of the crude extract on cellulose pulp biobleaching

Abstract: The ability of xylanolytic enzymes produced by Aspergillus fumigatus RP04 and Aspergillus niveus RP05 to promote the biobleaching of cellulose pulp was investigated. Both fungi grew for 4-5 days in liquid medium at 40 degrees C, under static conditions. Xylanase production was tested using different carbon sources, including some types of xylans. A. fumigatus produced high levels of xylanase on agricultural residues (corncob or wheat bran), whereas A. niveus produced more xylanase on birchwood xylan. The optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 24 publications
1
30
1
Order By: Relevance
“…These are very interesting results when compared to A. fumigatus xylanase described by Antony et al [15], which lost activity gradually after 30 min at 50°C, and at 60°C, a rapid loss of activity was observed with half-life for deactivation of 12 min. However, other A. fumigatus strains are described with good stability levels at 60°C [29,30]. Even though, our results suggest that endo-β-1,4-xylanase in the extract here obtained seems to be thermophilic, considered ideal for many biotechnological processes, being stable at 60°C over 1-h incubation period and presenting a half-life of 90 min.…”
Section: Partial Crude Enzyme Characterizationcontrasting
confidence: 64%
See 1 more Smart Citation
“…These are very interesting results when compared to A. fumigatus xylanase described by Antony et al [15], which lost activity gradually after 30 min at 50°C, and at 60°C, a rapid loss of activity was observed with half-life for deactivation of 12 min. However, other A. fumigatus strains are described with good stability levels at 60°C [29,30]. Even though, our results suggest that endo-β-1,4-xylanase in the extract here obtained seems to be thermophilic, considered ideal for many biotechnological processes, being stable at 60°C over 1-h incubation period and presenting a half-life of 90 min.…”
Section: Partial Crude Enzyme Characterizationcontrasting
confidence: 64%
“…Our results are comparable to other endo-β-1,4-xylanases produced by other strains of A. fumigatus. Maximum xylanolytic enzyme activity around 60-65°C has been cited [15,28]; however, it must be noticed that higher values such as 70°C [29], or even 90°C [25], have also been described for different strains of A. fumigatus.…”
Section: Partial Crude Enzyme Characterizationmentioning
confidence: 95%
“…This stability in acid pH values shows the potential application of such enzyme in industrial bioprocesses such as the production of bioethanol (PEIXOTO-NOGUEIRA et al, 2009). The xylanase enzyme also showed high stability up to 55 °C ( Figure 3D) and kept 86% of the maximum activity at 50 °C, indicating a higher stability when compared to other studies (KALOGERIS et al, 2003;KANG et al, 2004).…”
Section: Resultsmentioning
confidence: 73%
“…A comparison among the results of this study and those using other xylanases is difficult, due to differences in the origin and characteristics of the pulp, differences in pulp pretreatment, different processing conditions, and also due to enzyme characteristics. The reduction obtained in the treatments with P. janczewskii xylanases was higher than to those obtained with some other fungal xylanases, which normally present reductions between 0.9 and 4.6 units in kappa number Madlala et al 2001;Maximo et al 1998;Medeiros et al 2007;Michelin et al 2010;Nair et al 2010;Peixoto-Nogueira et al 2009;Taneja et al 2002). Only one study reported greater reduction, i.e., 10.0, treating a cellulose pulp with A. niger xylanases (Raghukumar et al 2004).…”
Section: Biobleachingmentioning
confidence: 95%